The Psychology of Collective Narcissism Insights from Social Identity Theory - Golec de Zavala, Agnieszka (Taylor & Francis, 2024)
The Psychology of Collective Narcissism is a ground-breaking text that presents a new theory of collective narcissism, a belief that exaggerated greatness of one's own group should be but is not sufficiently appreciated by others. The book presents this concept against the background of social identity theory and research. It explores antecedent as well as social and political consequences of collective narcissism. The author discusses how this burgeoning theory and research can help to elucidate a wide range of psychological dynamics involved in pressing societal issues, such as the declining appeal of democracy, increasing populism, decreasing social solidarity, increasing societal polarization and prejudice, intergroup hostility and political violence, social inequality, and fake news and belief in conspiracy theories. Also referring to societal problems exacerbated by the COVID-19 pandemic, this highly topical work explores socially shared beliefs as risk factors when predicting responses to crises and highlights conditions in which collective narcissism can be expected. The author also reviews research on interventions reducing the link between collective narcissism, prejudice, and retaliatory intergroup hostility focusing on her recent research on mindfulness. This is a valuable read for academics and students in psychology and the social sciences, those interested in societal processes as well as professionals dealing with the impact of collective narcissism. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.